Improving Transition Behaviors in Students With Autism Spectrum Disorders: A Comprehensive Evaluation of Interventions in Educational Settings. (July 2015) - Lequia, Jenna; Wilkerson, Kimber L.; Kim, Sunyoung; Lyons, Gregory L.
Students with autism spectrum disorders (ASD) often exhibit rigidity, which can lead to difficulties with transitions. Such difficulties can explain why students with ASD are placed in more restrictive educational environments. This review offers a quantitative synthesis of effects of interventions aimed to improve transitions of students with ASD and provides a descriptive overview of the quality of the included studies. Analyses focused on the main component of the intervention, topography of challenging behavior, and the type of transition expected of students with ASD. Activity schedules were most prominently used and most successful to ease transition difficulties. Strategies that align with preferences of students with ASD also successfully improved transitions. Practical implications and suggestions for future research are provided.